Potato Kenya: Climate change risks and opportunities - Bolt, Jaclyn; Demissie, Teferi Dejene; Duku, Confidence; Groot, Annemarie; Recha, John W.M. (2019)
Agriculture in Kenya contributes to the national economy, food security, and employment of rural households. Climate change and weather variability affect agricultural production negatively and it is expected to worsen in the future. Climate-smart agriculture (CSA) practices present an opportunity to reduce such losses, build resilience in the agriculture sector, improve productivity and farmer incomes, and contribute to climate change mitigation (CIAT & World Bank, 2017). In Kenya, potato is grown by about 800,000 farmers cultivating about 161,000 hectares per season with an annual production of about 3 million tonnes in two growing seasons. Beyond the farm, the industry employs about 3.3 million people as market agents, transporters, processors, vendors and exporters (Muthoni, Nyamongo, & Mbiyu, 2017).